2021
DOI: 10.1088/2053-1591/abd666
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of CuO NPs, characterization and their toxicity potential against HepG2 cells

Abstract: In this study, copper oxide nanoparticles (CuO NPs) were green synthesized using the leaf extract of Momordica cochinchinensis (Lour.). Various characterization techniques such as Energy-dispersive x-ray spectroscopy (EDS), Ultraviolet Visible (UV–vis) Spectroscopy, x-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and Fourier-transform Infrared (FTIR) Spectroscopy were utilized to study the formation of CuO NPs. DLS and TEM analysis revealed the formation of sphere-shaped CuO NPs with mean parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…), observing a zeta potential of −24 mV and a hydrodynamic diameter of 56 nm. 82 The comparisons with prior studies highlight the importance and reliability of the obtained zeta potential and hydrodynamic size values in our study, further confirming the suitability of the synthesized nanoparticles for specific applications in accordance with the objectives of this investigation.…”
Section: Resultssupporting
confidence: 88%
“…), observing a zeta potential of −24 mV and a hydrodynamic diameter of 56 nm. 82 The comparisons with prior studies highlight the importance and reliability of the obtained zeta potential and hydrodynamic size values in our study, further confirming the suitability of the synthesized nanoparticles for specific applications in accordance with the objectives of this investigation.…”
Section: Resultssupporting
confidence: 88%
“…Various experiments indicated that CuONPs could induce ROS generation in different cancer cells, including HepG2 93 , SK-Hep-1 12 , K562 17 , tumor-initiating cells-enriched PANC1 15 , and MCF-7 cells 78 . In another study, the incubation of HepG2 cancer cells with biosynthesized CuONPs at concentrations of 25–100 μg/mL for 48 h resulted in the elevation of ROS generation, compared to control cells 64 .
Figure 12 ROS levels in ( A ) MCF7 and ( B ) SKBR3 cell lines treated with IC 50 concentration of BC-CuONPs after 48 h. ***:P < 0.001.
…”
Section: Resultsmentioning
confidence: 96%
“…Gnanavel et al’s study and Obaid et al’s investigation indicated that the synthesized CuONPs show great anticancer effects on HCT-116 and HT-29 cancer cell lines with the IC 50 value of 40 μg/mL for 24 h, which was close to the current study’s findings 62 , 63 . Moreover, an investigation showed that the cell viability of HepG2 cell lines had a significant decrease in time- and dose-depended manner after treatment with biosynthesized CuONPs using Momordica cochinchinensis 64 . Another study indicated that the IC 50 values of biosynthesized CuONPs using Annona muricata extract for AMJ-13 and MCF-7 cells were 17.04 and 18.92 µg mL −1 , respectively, which demonstrates that the uptake of CuONPs by cancer cells could trigger apoptosis 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the wide abundant of the medicinal plants and its costly effective, there is a considerable growth in the synthesis of copper oxide nanoparticles utilizing green chemicals. [10][11][12] Copper oxide nanoparticles have attracted interest among numerous metal nanoparticles because they exhibit mechanical and biological features using modern technologies 13 . Copper oxide nanoparticles have been discovered to be particularly effective in gas sensors, photocatalytic applications, and the biomedical sciences for the treatment of numerous disorders 14 .…”
Section: Introductionmentioning
confidence: 99%